IDENTIFIKASI MOLEKULER NEUTROPHIL GELATINASE ASSOCIATED LIPOCALIN (NGAL) PADA MODEL HEWAN TIKUS (Rattus norvegicus) YANG DIINDUKSI GAGAL GINJAL AKUT DENGAN GLISEROL - , AHMAD FAUZI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Examination standards that are commonly used to monitor the development of acute renal failure (ARF) such as serum levels of creatinine and urea are less sensitive and less specific. Biomarker that can be used for the detection of ARF earlier and accurately is neutrophil gelatinase-associated lipocalin (NGAL). The objective of this research was to identify NGAL as biomarker of acute renal failure by comparing the levels of serum ureum and creatinin in rats induced acute renal failure with 50% glycerol. Twelve male Wistar rats (Rattus norvegicus), 2 months of age with 150- 200 g body wight (bw), were divided into 2 groups. Group I as the control group (n=2) were injected with sterile distilled water 10 mL/kg bw intramuscular and group II (n=10) were injected with 50% glycerol 10mL/ kg bw intramuscular, (after 12 hours of fasting). At 0, 6, 12, and 24 hours after induction, blood were collected from retroorbitalis for analysis of urea, creatinine concentration and identification of NGAL. The rats in group II were necropsied every 2 rats and removed the kidney of each after time blood collection for histopathologic process and NGAL identification. The levels of creatinin and ureum were analyzed by independent t test. Identification of NGAL was conducted by one step reverse transcriptase (RT)-polymerase chain reaction (PCR) and sequencing. The renal histopathologic changes were examined with a microscope 400x magnification. The results showed that glycerol induction could elevated the levels of urea at 6 hours, 12 hours and 24 hours significantly in compared to the control group (p<0.05). Creatinine levels were increased significantly at 24 hours in compared to the control group (p<0.05). The expression of NGAL in kidney and blood samples could be detected at 6 hours, 12 hours and 24 hours after induction. Intramuscular injection of 50% glycerol in rats caused tubular cell necrosis, tubular lumen dilatation, eosinophilic mass in the tubular lumen, and mononuclear cell infiltration in the interstitial cells. In conclusion NGAL could be detected before increasing of creatinine levels and could be used as an early detection of ARF